Report of the proceedings of the presbytery of Stirling, relative to the North Church, at heir meeting on Tuesday, 31st December, 1844 (N.pl.)
From the Stirling Journal and Advertiser of 3d January 1845. In: Detailed Report of the debate in the town council of Stirling, ...